Methylene blue confers protection against hepatotoxicity induced by Cisplatin; the involvement of oxidative stress, apoptosis and NCOA4-mediated ferritinophagy - Marawan A. Elbaset; Bassim M. S. A. Mohamed; Passant E. Moustafa; Yosra Assem Hussien; Zeinab A. El-Gendy; Alyaa Farouk Hessin; Mohamed A. Mohamady Hussein; Reda MS Korany; Hany G. Attia; Ashraf Azar; Hany M. Fayed; Bassim (Molecular Biology Reports, 2026)

Unraveling the structural controls and tectonic history of the eastern Saudi Arabian Shield using remote sensing, geological and aeromagnetic data - Reda A.Y. El-Qassas; Ahmed M. Eldosouky; Mohamed A. Abd El‑Wahed; Mohamed Attia; Hanbing Ai; Ahmad.M. Al-Saleh; Saad S. Alarifi (Journal of Asian Earth Sciences, 2026)

Comparative Metabolomic Profiling and Gastroprotective Efficacy of Phoenix dactylifera L. Seed Extracts: Modulation of the Oxido-Inflammo-Apoptotic Axis in Gastric Ulcer Model - Zeinab A. El-Gendy; Sara M. Baraka; Shimaa Abdelazeem; Gehad A. Abdel Jaleel; Reda M. S. Korany; Mona A. Raslan (Journal of Pharmaceutical Innovation, 2026)

Inhibitory activity of D-tryptophan against colistin-resistant Salmonella enterica serovar Typhimurium isolated from dairy products: In vitro evaluation and application in a soft cheese model - Mahmoud Elafify; Amr M. Bakry; Radwa Reda Shata; Samah S. Abdellatif; Qisen Xiang; Samar Aly (Food Bioscience, 2026)

High-performance microporous carbon for efficient tartrazine dye adsorption: experimental investigation coupled with molecular dynamics simulation - Ayad F. Alkaim; Uday Abdul-Reda Hussein; Rehab Katan Aljamaly; Usama S. Altimari; Imad Ibrahim Dawood; Aseel M. Aljeboree (Environmental Science and Pollution Research, 2026)

Synthesis, 131I-radioiodination, and biodistribution of a novel nicotinonitrile derivative with in vitro antimicrobial and DNA gyrase inhibitory activities - Basant G. Salib; Basma M. Essa; Hesham A. Shamsel‐Din; Mohamed A. Motaleb; M. El-Tawoosy; Adli A. Selim; Sameh Ahmed Rizk; Ahmed Hassan Ibrahim Faraag; Mohamed A. Ali; Islam Yousif Mostafa; Reda Mansour; Salah S. Elyan; et al. (Molecular Diversity, 2026)

Withdrawal notice to “Detection of Enterocytozoon hepatopenaei in pond-cultured Litopenaeus vannamei shrimp: Unveiling the epidemiological significance of some invasive macrofauna, synergistic diagnostic approach and treatment trial” - Alaa Eldin Eissa; Rasha S.A. Abd El-Lateif; Eman M. Younis; Samia Alzentani; Eman H. Rashwan; Reda M. Korany; Reham H. Ragab; Suzan S. Abulelkasem; Mahmoud A. Elnakeeb; Emad Afiffi; Heba A. Abdel Hady; Eman M. Abouelhassan (Journal of Invertebrate Pathology, 2026)

WITHDRAWN: Detection of Enterocytozoon hepatopenaei in pond-cultured Litopenaeus vannamei shrimp: Unveiling the epidemiological significance of some invasive macrofauna, synergistic diagnostic approach and treatment trial - Alaa Eldin Eissa; Rasha S.A. Abd El-Lateif; Eman M. Younis; Samia Alzentani; Eman H. Rashwan; Reda M. Korany; Reham H. Ragab; Suzan S. Abulelkasem; Mahmoud A. Elnakeeb; Emad Afiffi; Heba A. Abdel Hady; Eman M. Abouelhassan (Journal of Invertebrate Pathology, 2026)

Host–virus miRNA crosstalk in ebola virus disease - Ahmed S. Doghish; Gharieb S. El-Sayyad; Hamdi Bendif; Ahmed I. Abulsoud; Aya Salman; Hend H. Mohamed; Akram N. Salah; Ghadir A. Sayed; Nourhan H. Elshami; Hebatallah Ahmed Mohamed Moustafa; Mohamed Bakr Zaki; Osama A. Mohammed; et al. (Folia Microbiologica, 2026)

The role of mitochondrial dysfunction, oxidative stress, and gender in cardiac fibrosis and vascular remodeling in an induced aged rat model with possible mitigation by eugenol nano-emulsion - Rawan H. Hanafi; Marwa S. Khattab; Sara M. Baraka; Saber Ibrahim; Samar H. Elsharkawy; Reda M. S. Korany (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Cardiac diseases are strongly associated with aging and pose a major threat to survival. This study evaluated the cardioprotective effects of oral eugenol and its nano-emulsion (20 mg/kg) in a D-galactose-induced aging model (300 mg/kg, i.p.) in male and female rats over 12 weeks. Particle size and zeta potential analyses confirmed the successful development of a stable, well-dispersed nano-emulsion system. At the end of treatment, echocardiography, biochemical assays, histopathology, and immunohistochemistry were performed. Cardiac dysfunction and dilatation were more pronounced in males than females following D-galactose administration, as evidenced by left ventricular internal diameter in diastole (LVIDd) and left ventricular internal diameter in systole (LVIDs), and reduced ejection fraction (EF) and fractional shortening (FS). Both eugenol and its nano-emulsion preserved cardiac architecture and mitigated histopathological alterations, including myofibrillar distortion, necrosis, vascular remodeling, and fibrosis. Treatment significantly reduced oxidative stress and mitochondrial dysfunction by restoring GSH, lowering MDA, and modulating the PINK1/Mfn2 pathway. Furthermore, eugenol and its nano-emulsion attenuated cardiac inflammation, apoptosis, and fibrosis through downregulation of TGF-β1, MMP-9, TNF-α, and caspase-3 expression. In conclusion, eugenol nano-emulsion demonstrates promising anti-aging potential against cardiac complications by regulating mitochondrial dynamics, mitophagy, oxidative stress, inflammatory and apoptotic responses, and the SIRT1/TGF-β/MMP9 signaling pathway.

Epstein-Barr virus-encoded microRNAs: central players in nasopharyngeal and gastric carcinoma pathogenesis - Rasha Abu-Khudir; Ahmed S. Doghish; Hend H. Mohamed; Nehal I. Rizk; Haidy Adel Fahmy; Salma Zaki Fayez; Yara Ashraf; Ayatallah Elgohary; Hager Nasser Selim; Moustafa Mahmoud Abdelaziz; Osama A. Mohammed; Sherif S. Abdel Mageed; et al. (Archives of Virology, 2026)

Epstein-Barr virus and human MiRNAs crosstalk: orchestrating latency, lytic cycle, and immune system modulation - Reda M. Mansour; Gharieb S. El-Sayyad; Mohamed Hemdan; Nehal I. Rizk; Sherif S. Abdel Mageed; Osama A. Mohammed; Ahmed Mahdy; Khaled Abuelhaded; Shimaa A. Farag; Reem K. Shahin; Yara A. Nassar; Hamed M. El-Shora; et al. (Folia Microbiologica, 2026)

Infection control and wound care innovations in plastic surgery: a multidisciplinary approach - Rasha Abu-Khudir; Ahmed S. Doghish; Reda M. Mansour; Ghadir A. Sayed; Nourhan H. Elshami; Hebatallah Ahmed Mohamed Moustafa; Wagiha S. Elkalla; Ahmed O. Abdulkader; Sherif S. Abdel Mageed; Osama A. Mohammed; Rabab S. Hamad; Ahmed I. Abulsoud; et al. (Folia Microbiologica, 2026)

Surveying Shared Marine Resources at a Regional Scale: Connectivity and Differentiation of Round Sardinella in Eastern Mediterranean - Alice Ferrari; Giusy Catalano; Valentina Crobe; Alessia Cariani; Emre Keskin; Pierluigi Carbonara; Loredana Casciaro; Reda M. Fahim; Sharif Jemaa; Savaş Kılıç; Myriam Lteif; Abdalnasser S. H. Madi; et al. (Fishes, 2026)
The round sardinella (Sardinella aurita Valenciennes, 1847) is a widely distributed migratory pelagic fish inhabiting the Mediterranean Sea and the eastern Atlantic coasts. The species is heavily exploited and represents a valuable resource for global fisheries. In the Mediterranean area, uptakes of round sardinella are particularly high in the Ionian and Levant regions, where landings have shown fluctuating yet significant peaks in recent decades. Given its migratory nature, understanding the connectivity among populations is crucial for delineating appropriate fishery management units. Previous studies employing morphometric, meristic, and molecular analyses have yielded mixed results regarding population structuring. Here, the genetic differentiation among Eastern Mediterranean S. aurita populations was investigated using a multi-marker approach: the mitochondrial cytochrome c oxidase subunit I (COI), cytochrome b (CytB), control region (CR), and 16S ribosomal RNA (16S rRNA), and seven species-specific nuclear simple sequence repeats (SSRs). Overall, the results indicate high genetic diversity coupled with weak population structuring across the Eastern Mediterranean. These analyses aim at clarifying stock boundaries towards supporting sustainable management strategies at a regional scale for this ecologically and economically important species.

First report on spermatogenesis and spermatozoon ultrastructure of the Proteocephalidean cestode Ophiotaenia tessellata Gamil & Fouad, 2023, an intestinal cestode of colubrid snake Natrix tessellata (Laurenti, 1768) from Egypt - Irene S. Gamil; Reda M. Mansour (Zoomorphology, 2026)

Investigating the hepatoprotective effects of Onopordum cyrenaicum : phytochemical, biological, and computational approaches to combat liver damage - Fatma A. Elshibani; Amr Farouk; Dina Mostafa Mohammed; Reda M. S. Korany; Ghassan M. Sulaiman; Abdulnaser Kh. Abdulkarim; Nada A. Alzunaidy; Hamdoon A. Mohammed (Natural Product Research, 2026)

Repurposing rupatadine to attenuate ovarian ischemia reperfusion in rats through modulation of PAF/NF-κB/TNF-α/IL-1β; HIF-1α/VEGF/Caspase 3 signaling pathways - Hanaa Mohamed Khalaf; Sara M. Ahmed; Alyaa Abdelfattah Abdelmonaem; Rabeh Khairy Saleh; Abdelaleem Abdelnour Mohamed; AbdelHamid Sayed AboBakr Ali; Mohamed Adel; Heba Reda Mohamed; Heba S. Kamel; Walaa Yehia Abdelzaher (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
The aim of the current study is to identify the possible protective effect of rupatadine (RUP) on ovarian ischemia reperfusion (OIR) in rats. RUP was administered in the presence and absence of OIR. Thirty-two adult Wistar albino female rats were randomly arranged into four groups: Sham, RUP (6 mg/kg/day) for 14 days, OIR and OIR + RUP groups.The results demonstrated that OIR significantly lowered serum anti-mullerian hormone level and ovarian total antioxidant capacity. Besides, a significant elevation in serum follicle stimulating hormone, lutenizing hormone, ovarian malondialdehyde level, hypoxia-inducible factor-1(HIF-1α), platelet activating factor (PAF), tumor necrosis factor-alpha (TNF-α), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and interleukin 1beta (IL-1β) levels along with an evident increase in ovarian vascular endothelial growth factor (VEGF) and caspase-3 immunoexpression. While, OIR + RUP pretreated group showed a reversal in OIR damaging effects in a significant manner in all the aforementioned parameters. Based on these findings; RUP has powerful anti-IR actions by lowering oxidative stress, inflammation, and apoptosis via modulation of the PAF/ NF-κB/TNF-α/ IL-1β; HIF-1α/ VEGF / Caspase 3 signaling pathways. Graphical abstract

Cerium oxide nanoparticles attenuate hepatic failure via blocking TGF-β/Smads and upregulating Nrf2/HO-1 signaling pathways in liver fibrosis rat model - Noha A. Mowaad; Sara M. Baraka; Saber Ibrahim; Doaa A. Mansour; Reda M. S. Korany; Ahmed F. El-Sayed; Arwa A. Hassan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
T his article is aimed at assessing the anti-fibrotic action of plant-based fabricated cerium oxide nanoparticles (CeO 2 NPs). The Carissa carandas aerial parts methanolic extract was utilized to prepare CeO 2 NPs, where the dispersal of particle size distribution and zeta potential value was 61.9 nm and − 18.94 mV, respectively, verifying the successful synthesis of CeO 2 NPs. In rats, CeO 2 NPs were intravenously injected at doses of 0.1 and 0.5 mg/kg twice a week for a month, in parallel with thioacetamide (TAA, 200 mg/kg, i.p). Our findings revealed that CeO 2 NPs alleviated the alteration in serum GPT, GOT, ALP, total bilirubin, albumin, and total protein levels induced by TAA. Additionally, the hepatic oxidative insult due to TAA was inferred by elevation in malondialdehyde and reduction of glutathione content, which in combination with downregulation of SIRT1, Nrf2, and HO-1 in hepatic tissues was improved by CeO 2 NPs. A clear repression in hepatic fibrosis was observed in CeO 2 NP-treated groups as demonstrated by significant downregulation in TGF-β1 and p-Smad 2 and 3 proteins and COL1A1, MMP-2, and α-SMA expressions in hepatic tissues. The histopathological outcomes exhibited a considerable accumulation of collagen fibers in hepatocytes in TAA-challenged rats, which was ameliorated by CeO 2 NPs. Also, CeO 2 NPs dampened the death of hepatic cells via blocking caspase 3 activation as indicated by the immunohistochemical results. The in silico investigations documented the powerful binding affinities of TGF-β1, COL1A1, MMP-2, p-Smad2, p-Smad3, SIRT1, Nrf2, and HO-1 proteins with CeO 2 NPs. In conclusion, this study emphasized the efficacy of CeO 2 NPs as a potent anti-fibrotic agent through upregulating SIRT1/Nrf2/HO-1 and downregulating TGF-β1/Smads pathways.

MiRNA Dysregulation in Epilepsy: Bridging Molecular Mechanisms and Therapeutic Innovation - Reda M. Mansour; Hend H. Mohamed; Khaled M. Alam-Eldein; Mohamed Hemdan; Nehal I. Rizk; Osama A. Mohammed; Youssef A. Doghish; Mariam O. Abbass; Moaz Mohsen Shafey; Moustafa Mahmoud Abdelaziz; Mohamed H. A. Gadelmawla; Amal Ahmed Mohamed; et al. (Molecular Neurobiology, 2026)

miRNAs in Amyotrophic Lateral Sclerosis: Tiny Molecules, Tremendous Impact - Sherif S. Abdel Mageed; Ghadir A. Sayed; Ahmed Mahdy; Walaa A. El-Dakroury; Ahmed O. Abdulkader; Hebatallah Ahmed Mohamed Moustafa; Reda M. Mansour; Osama A. Mohammed; Mohammed S. Elballal; Ahmed E. Elesawy; Ahmed S. Doghish (Molecular Neurobiology, 2026)

Metabolomics profiling and neuroprotective effects of Lagerstroemia loudonii leaf extract and its kleptose Crysmeb®- stabilized loaded nanosuspension in seizure mice model - Sara M. Baraka; Nesma M.E. Abo El-Nasr; Rabab Kamel; Marwa M. Elbatanony; Omar A. Ahmed-Farid; Reda M. S. Korany; Salma A. El Sawi; Amal A. Maamoun (Metabolic Brain Disease, 2025)
This research was designed to explore the anti-epileptic action of the ethanolic leaf extract of Lagerstroemia loudonii (LLE) compared to the extract-loaded MβCD-stabilized nanosuspension (MβCD-NS). UPLC–ESI–QTOF –MS/MS analysis of LLE revealed the identification of 57 compounds; phenolics were the major recorded class. Nanosuspensions were prepared and examined; the particle size of the selected physically stable MβCD-NS was 445.8 ± 61.08 nm with a uniform size distribution and an almost spherical outline as shown by TEM. Based on the acute toxicity results, LLE or MβCD-NS was orally gavage at doses of 100 and 200 mg/kg. Convulsions were induced by maximum electric shock (MES, 35 mA, 3 s), and pentylenetetrazole (PTZ, 85 mg/kg i.p) in mice. MβCD-NS (200 mg/kg) demonstrated significant anticonvulsant effects, including complete protection% in MES study and low tonic convulsion score in PTZ-model. PTZ injection instigated locomotor deficits, oxidative and nitrosative insults, neuroinflammation, imbalance in brain neurotransmitters viz. dopamine, serotonin, norepinephrine, GABA, glutamate, and severe structural changes in the brain. However, LLE and MβCD-NS (200 mg/kg) ameliorated all these alterations through preserving antioxidant defense mechanisms by improving GSH content, and Nrf2 immuno-expression, as well as reducing MDA, NO, and GSSG levels in the brain. MβCD-NS restored the brain neurotransmitter levels that involved in the observed improvement in the animals’ locomotor activity. The detected low TNF-α immuno-expression of the brain regions of the MβCD-NS group highlighted its anti-inflammatory action. In conclusion, MβCD-NS exhibited superior anti-epileptic potential by counteracting neuronal oxido-inflammatory damage, positioning it as a promising therapeutic strategy for epilepsy. Graphical Abstract

Crosstalk between miRNAs and oxidative stress: implications for cancer pathogenesis and therapy - Reda M. Mansour; Mohamed Hemdan; Khaled M. Alam Eldein; Al-Aliaa M. Sallam; Hanan A. Elimam; Ola Elazazy; Sherif S. Abdel Mageed; Osama A. Mohammed; Nehal I. Rizk; Moustafa Mahmoud Abdelaziz; Moaz Mohsen Shafey; Nawal Osama Amin Mohamed; et al. (Functional & Integrative Genomics, 2025)

SNP’s use as a potential chemotoxicity stratification tool in breast cancer: from bench to clinic - Hebatallah Ahmed Mohamed Moustafa; Walaa A. El-Dakroury; Alaa Ashraf; Ahmed I. Abulsoud; Shereen Saeid Elshaer; Nourhan M. Abdelmaksoud; Nehal I. Rizk; Sherif S. Abdel Mageed; Mohamed Bakr Zaki; Reda M. Mansour; Osama A. Mohammed; Mai A. Abd-Elmawla; et al. (Functional & Integrative Genomics, 2025)

miRNAs and their multifaceted role in cutaneous wound healing - Reda M. Mansour; Sherif S. Abdel Mageed; Farah A. Awad; Mohamed M. Sadek; Shehab Ahmed Adel; Alaa Ashraf; Khaled M. Alam-Eldein; Nada E. Ahmed; Rana Y. Abdelaziz; Esraa Farid Tolba; Hend H. Mohamed; Nehal I. Rizk; et al. (Functional & Integrative Genomics, 2025)

From fatty liver to fibrosis: the impact of miRNAs on NAFLD and NASH - Reda M. Mansour; Sherif S. Abdel Mageed; Ahmed I. Abulsoud; Ghadir A Sayed; Radwa H. Lutfy; Farah A. Awad; Mohamed M. Sadek; Abanoub A. S. Shaker; Osama A. Mohammed; Mustafa Ahmed Abdel-Reheim; Hanan Elimam; Ahmed S. Doghish (Functional & Integrative Genomics, 2025)

Microbiota-based therapies in oral health and disorders - Akram N. Salah; Youssef A. Doghish; Shaimaa O. Abbass; Reda M. Mansour; Ghadir A. Sayed; Nourhan H. Elshami; Sherif S. Abdel Mageed; Osama A. Mohammed; Ahmed I. Abulsoud; Mohamed Bakr Zaki; Esraa M. Mosalam; Mahmoud A. Elrebehy; et al. (Folia Microbiologica, 2025)
The human oral microbiome is a complex, dynamic ecosystem critically involved in maintaining oral health and contributing to systemic well-being. Many bacteria and fungi are involved in oral cavities such as Penicillium , Rhodotorula , Saccharomycetales , Streptococcus , Veillonella , Neisseria , Actinomyces , and Schizophyllum. Disruption of microbial homeostasis, or dysbiosis, underpins a wide spectrum of oral diseases, including dental caries, periodontal disease, endodontic infections, and mucosal conditions. Recent advances in microbiome research have elucidated the mechanisms by which pathogenic microbial consortia, such as the red complex ( Porphyromonas gingivalis , Tannerella. forsythia , and Treponema denticola ), synergistically promote disease progression through virulence factors, metabolic interactions, and biofilm formation. Emerging microbiome-based therapies, comprising probiotics, postbiotics, predatory bacteria, and using bacteriophages, offer promising adjuncts or alternatives to traditional antimicrobial approaches by restoring microbial balance, reducing pathogenic load, and modulating host immune responses. For instance, probiotic strains like Streptococcus salivarius and Lactobacillus spp. have demonstrated efficacy in reducing plaque, gingival inflammation, and pathogenic bacteria, as well as having significant immunological modulation, while postbiotics provide similar benefits with enhanced safety and stability. Additionally, predatory bacteria such as Bdellovibrio bacteriovorus show potential for selective bacterial elimination and combating periodontal diseases that are driven by Gram-negative anaerobes. Bacteriophages offer another precision tool for targeting oral pathogens by lysing bacteria upon replication. Finally, oral microbiota transplantation aimed at treating periodontal disease by restoring a balanced microbial community in the oral cavity. These innovative strategies, combined with a nuanced understanding of biofilm dynamics and host–microbe interactions, pave the way for personalized and ecologically sustainable oral health interventions. Continued research is essential to translate these promising approaches into clinical practice, optimize delivery systems, and elucidate long-term safety and efficacy.

Blue-green pigment production by environmental isolates of Pseudomonas aeruginosa: Purification and bioactivity - Wael Mohamed Ali; Wesam A. Hassanein; Fifi M. Reda; Mohamed A. A. Ahmed; Heba shawky; Rofaida S. Abd Elkader (Folia Microbiologica, 2025)

miRNA dysregulation in depression: unraveling the interplay between neuroplasticity, HPA axis dysfunction, and neuroinflammation - Reda M. Mansour; Nehal I. Rizk; Sherif S. Abdel Mageed; Khaled M. Alam-Eldein; Haidy Adel Fahmy; Radwa H. Lutfy; Moaz Mohsen Shafey; Hend H. Mohamed; Mohamed M. Nazmy; Shimaa A. Farag; Moustafa Mahmoud Abdelaziz; Shehab Ahmed Adel; et al. (Metabolic Brain Disease, 2025)

Epidemiological tracking and control strategies of early mortalities in hatchery-reared gilthead seabream (Sparus aurata) larvae - Alaa Eldin Eissa; Rabia El Ziltne; Asmaa Edrees; Asmaa O. El-Ramlawy; Mahmoud S. Sharaf; Reda Korany; Hany M. R. Abdel-Latif; Ibrahim Hassan Ibrahim; Abeer E. Mahmoud; Rehab Qorany; Shimaa Mansour; Sarah A. A. Ibrahim; et al. (Aquaculture International, 2025)
Implementing competent biosecurity strategies is a key factor for maintaining a disease-free aquaculture. Bacterial infections are an eminent threat to all live stages occurring in the marine hatchery. Live foods, including algae, rotifers, and artemia, are potential sources of microbial infections in hatcheries with ineffectual biosecurity plans. In the present study, epidemiological, bacteriological, molecular, and histopathological investigations were carried out on all critical live components of the marine hatchery, including batches of algal cultures, rotifers ( Brachionus plicatilis ), artemia ( Artemia salina ), eggs, cultured gilthead seabream ( Sparus aurata ) larvae, and other inanimate components such as water supply. Clinically, fish larvae had pale skin and exhibited sluggish and frequent erratic swimming patterns. Two Vibrio isolates were presumptively identified by using the API 20E system. After molecular screening and phylogenetic analysis, these isolates were confirmed to be V. alginolyticus and V. vulnificus . Remarkably, V. alginolyticus was the most commonly recovered species from seawater, eggs, algae, rotifers, and artemia cultures. Both of these Vibrio isolates exhibited diverse sensitivities to different antibiotics used in the antibiogram, with maximal susceptibility to florfenicol. Therapeutic and preventive programs were imposed at different rearing stages after tracing the potential sources of infection.

Replacing fishmeal with Palaemon serratus meal enhances growth, carcass traits, digestive enzymes, immune-physiological response, antioxidants, and inner organ histopathology of Dicentrarchus labrax - Toqa S. M. Saif; Hatem H. Mahmoud; Ashraf I. G. Elhetawy; Reda M. Fahim; Hosam E. Elsaied; Mohamed M. Abdel-Rahim (Aquaculture International, 2025)
The aquaculture industry is currently facing significant challenges due to the increasing demand for fishmeal (FM), which is an indispensable ingredient in marine aquaculture. This study aims to reduce the reliance on fishmeal in marine fish nutrition and replace it with natural low-trophic animal sources that are more sustainable and of comparable nutritional value to those of fishmeal. Six levels of Palaemon serratus (PS) meal were tested in triplicate: 0, 10, 20, 30, 40, and 50% as a replacement for fishmeal, designated PS0, PS10, PS20, PS30, PS40, and PS50, respectively. A total of 216 apparently healthy Dicentrarchus labrax juveniles (average weight 8.75 ± 0.05 g) were randomly allocated to 18 circular fiberglass tanks. The fish were fed the experimental diet (42.75% protein) for 60 days. The results revealed a better water quality indicator (more oxygen and less ammonia) among the PS -tested treatments. The groups fed PS -supplemented diets outperformed the control group in terms of growth and feed utilization indicators, with the PS40 group performing best. A polynomial second-order regression model was employed to get the optimal results in diets which containing 42.5% PS meal for SGR and 38.5% PS for FCR. Compared with those in the PS0 group, immune-related parameters such as IgM, total protein, and total albumin increased by 18.1%, 38.5%, and 41.4%, respectively. The serum lipid profile was better in the PS30 and PS40 groups, whereas digestive enzymes were better in the PS40 and PS50 groups. PS replacement increased serum growth and immune hormone levels. Intestinal and liver histomorphology revealed that increasing the PS replacement rate enhanced sea bass health. Sea bass diets are recommended to replace 40% of fishmeal with P. serratus meal.

Exploration of Novel Pyrazole Derivatives: Design, Synthesis, and Integrated Biological Profiling (In Vitro and In Silico) of Their Antioxidant, Antibacterial, and Antimitotic Properties - Muneera S. M. Al-Saleem; Yousef E. Mukhrish; Bharath Kumar Chagaleti; Jehan Y. Al-Humaidi; Kathiravan MK; Ali Oubella; Reda A. Haggam (Journal of Fluorescence, 2025)

MMP-9 Expression in bone cells in the developing femur - Fatma El-Zahraa A. Mustafa; Hanan H. Abd-Elhafeez; Reda S. taha; Amira Osman; Mohamed M. Almaki; Zyad Mohamed Baker; Abdullah A.A. Alghamdi; Diaa Massoud; Mohamad Elmasry; Soha A. Soliman; Abeer Madkour Mahmoud (Tissue and Cell, 2025)

MicroRNAs in HIV infection: dual regulators of viral replication and host immunity - Reda M. Mansour; Gharieb S. El-Sayyad; Nehal I. Rizk; Sherif S. Abdel Mageed; Mohamed Salah Basiouny; Salma A. El-Sayed; Salma Zaki Fayez; Moustafa Mahmoud Abdelaziz; Khaled Abuelhaded; Haidy Adel Fahmy; Osama A. Mohammed; Mustafa Ahmed Abdel-Reheim; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The Role of MicroRNAs in Neurodegeneration: Insights from Huntington’s Disease - Reda M. Mansour; Abanoub A. S. Shaker; Ahmed I. Abulsoud; Sherif S. Abdel Mageed; Alaa Ashraf; Elsayed G. E. Elsakka; Mohammed. I. Dahab; Mohamed M. Sadek; Farah A. Awad; Radwa H. Lutfy; Hanan Elimam; Ahmed H. I. Faraag; et al. (Molecular Neurobiology, 2025)

Pathogen Partnerships or Power Struggles? Pseudomonas aeruginosa, and Staphylococcus aureus Dynamics in Cystic Fibrosis - Neveen M. Saleh; Esraa S. F. Sudan; Sara H. Mohamed; Maram M. El-Shahed; Reda E. Hamouda; Ahmed Osama El-Gendy; Ahmed A. Farag (Current Microbiology, 2025)

Microbiological and physiological impacts of coconut oil microcapsule powder supplementation on Liza ramada - Mohammed F. El Basuini; Maha Elanany Yahia; Abdelaziz M. El-Hais; Ali A. Soliman; Islam I. Teiba; Mohamed Reda Badr; Mohamed A.A. Zaki; Amr I. Zaineldin; Ibrahim T. El-Ratel; Mahmoud S. Gewaily; Mayada Alhoshy; Akram Ismael Shehata (Aquaculture, 2025)

Therapeutic applications of natural products in the management of venous diseases: a comprehensive review - Rasha E. Mostafa; Dalia E. Ali; Riham A. El-Shiekh; Ahmed N. El-Alfy; Mohamed S. Abd El Hafeez; Ahmed M. Reda; Nesrin M. Fayek (Inflammopharmacology, 2025)
The occurrence of venous diseases among adults is approximately 77% in females and 57% in males. These conditions are prevalent, progressive disorders that significantly affect individuals socially, physically, and psychologically, often resulting in various venous abnormalities that hinder effective blood circulation in the lower limbs. This review provides a comprehensive overview of venous diseases, focusing on their pathophysiology, symptoms, causes, risk factors, diagnosis, and complications. The symptoms associated with venous diseases are diverse and can include pain, heaviness, swelling, ulcers, and skin changes. Risk factors such as age, obesity, hormonal influences, and genetic predispositions are discussed in relation to their contribution to disease progression. The therapeutic modalities for managing venous diseases are explored, with a particular emphasis on natural products in alleviating symptoms and improving vascular health. Natural compounds, i.e., flavonoids, play a vital role in the circulatory system, supporting blood vessels and promoting healthy blood flow, in addition to their vasoprotective, antioxidant, anti-inflammatory, and anti-platelet properties. Overall, the ongoing research efforts on the efficacy of natural products will significantly enhance the management of several venous diseases in the coming years.

Metabolomics analyses and comparative insight to neuroprotective potential of unripe fruits and leaves of Citrus aurantium ethanolic extracts against cadmium-induced rat brain dysfunction: involvement of oxidative stress and akt-mediated CREB/BDNF and GSK3β/NF-κB signaling pathways - Doaa A. H. Deabes; Eman A. W. El-Abd; Sara M. Baraka; Zeinab A. El-Gendy; Reda M. S. Korany; Marwa M. Elbatanony (Metabolic Brain Disease, 2025)
Serious neurological disorders were associated with cadmium toxicity. Hence, this research aimed to investigate the potential neuroprotective impacts of the ethanolic extracts of Citrus aurantium unripe fruits and leaves (CAF and CAL, respectively) at doses 100 and 200 mg/kg against cadmium chloride-provoked brain dysfunction in rats for 30 consecutive days. HPLC for natural pigment content revealed that CAF implied higher contents of Chlorophyll B, while the CAL has a high yield of chlorophyll A and total carotenoid. Fifty-seven chromatographic peaks were identified by UPLC/MS / MS; 49 and 29 were recognized from CAF or CAL, respectively. Four compounds were isolated from CAF: 3’,4’,7 –trihydroxyflavone, isorhainetin, vitexin, and apigenin. In vitro studies outlined the antioxidant capacity of studied extracts where CAF showed better scavenging radical DPPH activity. Results clarified that both extracts with a superior function of CAF at the high adopted dose significantly ameliorated CdCl 2 -induced neuro-oxidative stress and neuro-inflammatory response via restoring antioxidant status and hindering nuclear factor kappa B (NF-κB) stimulation. Moreover, it up-regulated the levels of phospho-protein kinase B (p-Akt), phospho- cAMP-response element binding protein (p-CREB), and brain-derived neurotropic factor (BDNF) levels, and elicited a marked decrease in the content of glycogen synthase kinase 3 beta (GSK3β), besides amending Caspase-3 and hyperphosphorylation of tau protein in brain tissues. Moreover, a significant improvement in the rats’ behavioral tasks of the CAL and CAF-treated groups has been recorded, as indicated by marked preservation in locomotion, exploratory, and memory functions of the experimental rats. In conclusion, the reported neuroprotective impacts of C. aurantium extracts may be through modulating p-AKT/p-CREB/BDNF and / or p-Akt/ GSK3β/NF-κB signaling pathways.

Ethyl formate as a fumigant to control the stored date insects in a prototype and its impact on date fruit quality - Mahmoud M. Abo-El-Saad; Yasser H. Hegazi; Mohamed S. Shawir; Reda K. Abdel-Razik; Nadia A. Hamed; Nawal Abdulaziz Alfuhaid; Gomaa R.M. Ramadan (Journal of Stored Products Research, 2024)

Exploring the clinical potential of circulating LncRNAs in breast cancer: insights into primary signaling pathways and therapeutic interventions - Tohada M. AL-Noshokaty; Rehab Abdelhamid; Tasnim Reda; Ayat Alaaeldien; Nourhan Abdellatif; Abdallah Mansour; David Gendi; Nourhan M. Abdelmaksoud; Shereen Saeid Elshaer; Ahmed S. Doghish; Mohamed Hossam Sobhy; Osama A. Mohammed; et al. (Functional & Integrative Genomics, 2024)

Assessment of biochemical biomarkers and environmental stress indicators in some freshwater fish - Salwa M. Abdallah; Reham E. Muhammed; Reda El. Mohamed; Hala El Daous; Dina M. Saleh; Mohamed A. Ghorab; Shaohua Chen; Gharieb S. El-Sayyad (Environmental Geochemistry and Health, 2024)
The mechanism by which an organism can adapt to subtle environmental changes is predicated on modifications to biochemical processes within the cellular metabolism in response to such changes. Changes in these processes have the potential to induce alterations in cellular structures and tissue organization, as well as establish a causal link between fluctuations in these parameters and stressors exposure. This investigation's main goal and innovation is to evaluate the environmental stress indicators in the aquatic ecosystem of Lake Qarun. Pesticide residues in freshwater fish should be the primary focus of evaluation of environmental stressor concentrations, since they serve as bioindicators at different times and places on a spatiotemporal scale. A thorough analysis of suggestive biochemical biomarker reactions should also be conducted. The effects of environmental stressors, specifically pesticide contamination in Qarun Lake, have been observed and investigated in relation to two fish species: Solea aejabtiaca and Oreochronis niloticus . The results of a hazard assessment conducted at six sampling sites using spatio-temporal data revealed elevated mean values for the pesticides, persistent organic pollutants (POPs), organochlorines, organophosphates, and pyrethroids that were detected. A multi biomarker approach facilitates a more comprehensive understanding of stress responses induced by exposure to pollutants. As a result, the activities of the biochemical biomarkers CYP-450, GST, GSH, and LDH in the blood and liver of fish samples were found to be notably elevated. The suitability of the identified variables for biomonitoring of aquatic pollution was validated, and the data unveiled variations in sensitivity among species, implying that Nile tilapia could potentially function as a bioindicator with high sensitivity. The findings were correlated with the concentrations of detrimental organochlorines, organophosphorus, and pyrethroids in the muscles and gills. The data indicates that pollutants linked to agricultural wastes, runoff, and municipal effluent may be discharged into the lake ecosystem. Consequently, to safeguard the environment, it is essential to enforce and implement policies, acts, and regulations that already exist. Assessing the effects of additional environmental stressors on aquatic ecosystems is another way in which biomarker screening with an integrative approach improves our comprehension of how toxicants impact various levels of biological organization and is particularly useful in realistic environmental exposure scenarios.

Biological Selenium Nanoparticles in Quail Nutrition: Biosynthesis and its Impact on Performance, Carcass, Blood Chemistry, and Cecal Microbiota - Fayiz M. Reda; Mahmoud Alagawany; Ayman S. Salah; Mohamed A. Mahmoud; Mahmoud M. Azzam; Alessandro Di Cerbo; Mohamed T. El-Saadony; Shaaban S. Elnesr (Biological Trace Element Research, 2024)

Alterations in histopathology and stress-associated gene expression induced by infection with Prohemistomum vivax encysted metacercariae in Nile tilapia - Shimaa Abdelkhalek; Marwa M. Attia; Marwa A. Ibrahim; Reda M. S. Korany; Mohamed Abdelsalam; Dalia A. Abdel-moneam (Aquaculture International, 2024)
Due to limited data on the pathogenicity of Prohemistomum vivax ( P. vivax ) and its impacts on fish health, this study aimed to determine the morphological, molecular characteristics, pathogenicity, and histopathological alterations in fish infected with P. vivax . Eight hundred (800) Nile tilapia ( Oreochromis niloticus ) were collected from various farms in Kafr El Sheikh Governorate. The fish were examined for encysted metacercariae (EMC) in different organs. Tissue specimens were collected and underwent histopathological analysis, expression of stress-related genes, and genetic characterization by sequencing of the internal transcribed spacer 2 (ITS2). P. vivax metacercariae were oval to round in shape and were collected from various organs including the muscle, skin, eyes, intestine, liver, kidney, and gills of infected O. niloticus . Sequencing and phylogenetic analysis of the ITS2 region revealed a 507-bp fragment, confirming parasite identity and matching within the same clade as other P. vivax isolates. Infected fish displayed abdominal hydropsy, skin darkening, and emaciation. P. vivax encysted metacercariae were detected during the study period in 620/800 fish, with an overall prevalence of 77.5%. The seasonal prevalence was 95% in summer, 85% in spring, 55% in autumn, and 75% in winter. The intensity of infection was 1–40 cysts per microscopic field. Histopathological examination of muscles revealed parasitic cysts embedded within muscle fibers, causing severe degeneration and necrosis. Upregulation of cytochrome P450 (cpy1a1), heat shock protein 70 (hsp-70), and tumor suppressor p53 (p53) was recorded in both liver and muscle samples of infected tilapia compared to controls. This indicates activation of detoxification, cellular stress, and apoptotic pathways in response to P. vivax infection. There is limited data available on the pathogenicity of P. vivax and its impacts on fish health; thus, this study provides key insights into the morphology, pathogenicity, and histopathological impacts of P. vivax in Nile tilapia.

Use of irradiation against stored product insect species that infest edible insect rearing - Thanaa M. Sileem; Reda S. Hassan; Waheed A.A. Sayed (Journal of Stored Products Research, 2024)

Effectiveness of Epicoccum nigrum and Silver Nanoparticles in Controlling Chocolate Spot Disease and Enhancing Growth and Yield of Faba Bean (Vicia faba L.) - Mansour M. El-Fawy; Sherif A. Ahmed; Reda A. A. Korrat; Kamal A. M. Abo-Elyousr; Magdi A. A. Mousa; Omer H. M. Ibrahim; Ayman S. Saeed (Journal of Crop Health, 2024)

The digestible nutrient and energy values of diets across seven marine aquaculture species demonstrate the potential and limitations for cross utility of digestibility data - Asaad H. Mohamed; Joseph Laranja; Reda Saleh; Seemab Zehra; Paulo H. De Mello; Aboobucker S. Abul Kasim; Jorge Alarcon; Ali M. Alshaikhi; Abdulaziz M. Al-Suwailem; Brett D. Glencross (Aquaculture, 2024)

The record of Vannella species (Vannellidae, Discosea, Amoebozoa) from freshwater sources in Dakahlyia Governorate, Egypt - Asmaa M. Marzouk; Mohamed I. Mashaly; Enayat S. Reda; Mohamed M. El-Naggar (Archives of Microbiology, 2024)
The River Nile is the main source of fresh water in Egypt, where its water is used for irrigation, drinking, fisheries, industrial uses, and recreation. For sustainable utilization of the River Nile and its branches in the Nile Delta region, it is necessary to monitor regular investigation for the biodiversity of protozoan fauna in the Damietta branch and other freshwater canals in Dakahlyia Governorate. Water samples were collected monthly from different water sources, for 1 year, and examined for protozoans, using phase-contrast microscopy and recorded video films, The genus Vannella Bovee 1965 is recorded for the first time in four freshwater localities: Demietta branch of the River Nile, Mansouria Canal, Bouhia Canal, and Bahr El-Saghir Canal. A detailed morphological description with a brief report of their locomotion has been given for four morphologically different Vannella species. The locomotive form of Vannella sp.1 has a long pointed posterior tail and 2 lateral posterior processes. Such a tail was absent in other Vannella species. Vannella sp.2 is unique among other recorded species, where its locomotive form possesses a long posterior rounded tail region and a frontal hyaloplasm provided with a wavy surface that forms several lobes and finger-like processes during locomotion. In addition, the hyaloplasm produces several transverse waves that vary in thickness and density. The floating form of Vannella sp.2 is of a radial type and has comparatively long hyaline pointed and spiral pseudopodia. The process of transformation of locomotive form to floating form in Vannella sp.2 has been followed up using several recorded video films. The locomotive form of Vannella sp.3 is bear-shaped, while that of Vannella sp.4 has variable shapes from semicircular to rectangular and sometimes fan-shaped. During movement in vivo, locomotive cells of all Vannella species, except Vannella sp.1, move in nearly a straight line, but there were variations in their rate of locomotion. Vannella sp.4 recorded the highest rate (6.8 µm/s), followed by Vannella sp.2 (4.5 µm/s), Vannella sp.3 (2.4 µm/s), and finally Vannella sp.1 (1.0 µm/s). Molecular studies and transmission electron microscope examinations are still needed to confirm the precise identity of each Vannella species.

Decoration of viscose fibers with silver nanoparticle-based titanium-organic framework for use in environmental applications - Mohamed Rehan; Ahmed S. Montaser; Mahmoud El-Shahat; Reda M. Abdelhameed (Environmental Science and Pollution Research, 2024)
To effectively remove pharmaceuticals, nitroaromatic compounds, and dyes from wastewater, an efficient multifunctional material was created based on silver nanoparticles (Ag) and MIL-125-NH 2 (MOF) immobilized on viscose fibers (VF) as a support substrate. Firstly, silver nanoparticles (Ag) were immobilized on the surface of viscose fibers (VF) via in situ synthesis using trisodium citrate (TSC) as a reducing agent to create (VF-Ag). Then, VF and VF-Ag were decorated with the titanium metal–organic framework MIL-125-NH 2 (MOF) to create VF-MOF and VF-Ag-MOF. The influence of VF-Ag, VF-MOF, and VF-Ag-MOF on the sonocatalytic or sonophotocatalytic degradation of sulfa drugs was investigated. The results show that VF-Ag-MOF showed excellent sonocatalytic and sonophotocatalytic activity towards the degradation of sulfa drugs compared to VF-Ag and VF-MOF. Furthermore, sonophotodegradation showed a dramatic enhancement in the efficiency of degradation of sulfa drugs compared to sonodegradation. The sonophotodegradation degradation percentage of sulfanilamide, sulfadiazine, and sulfamethazine drugs in the presence of VF-Ag-MOF was 65, 90, and 95 after 45 min of ultrasonic and visible light irradiation. The catalytic activity of VF-Ag, VF-MOF, and VF-Ag-MOF was evaluated through the conversion of p-nitrophenol (4-NP) to p-aminophenol (4-AP). The results demonstrate that VF-Ag-MOF had the highest catalytic activity, followed by VF-Ag and VF-MOF. The conversion percentage of 4-NP to 4-AP was 69%. The catalytic or photocatalytic effects of VF-Ag, VF-MOF, and VF-Ag-MOF on the elimination of methylene blue (MB) dye were investigated. The results demonstrate that VF-Ag-MOF showed high efficiency in removing the MB dye through the reduction (65%) or photodegradation (71%) after 60 min. VF-Ag-MOF composites structure–activity relationships represent that doping within silver NPs enhanced the photocatalytic activity of MIL-125-NH 2 , which could be explained as follows: (i) Due to the formation of a Schottky barrier at the junction between MIL-125-NH 2 and Ag NPs, the photogenerated electrons in the conduction band of MIL-125-NH 2 were supposed to be quickly transferred to the valence band of the Ag NPs, and subsequently, the electrons were transferred to the conduction band of Ag NPs. This considerable electron transferring process, which is reported as Z scheme heterojunction, can efficiently suppress the recombination of electron/hole pairs in VF-Ag-MIL-125-NH 2 composites. (ii) Sufficient separation between the photogenerated charge carriers (holes and electrons) and avoiding their recombination enhanced the photocatalytic activity of composites.

Investigating the efficiency of bisphenol-A diglycidyl ether/resole phenol formaldehyde/polyamine blends as Cerium adsorbent from aqueous solution - Magd M. Badr; W.M. Youssef; Entessar M. Elgammal; Reda S. Abdel Hameed; M.M. El-Maadawy; A.E.M. Hussien (Journal of Environmental Chemical Engineering, 2023)

Effectiveness application of Chitosan/Alginic/Copper–organic framework beads on removal of carbaryl carbamate from wastewater - Reda M. Abdelhameed; Ahmed Rady; Abeer S. Elsherbiny; Ali H. Gemeay (Environmental Nanotechnology, Monitoring & Management, 2023)

Performance enhancement of hemispherical solar stills using different shapes of basin liners (sinusoidal and half-circle) incorporated with inverted solar collectors - Mohammed El Hadi Attia; Abd Elnaby Kabeel; Mohamed Abdelgaied; Reda S. Salama; Abd Elkader Abdallah; Moataz M. Abdel-Aziz; Yehia Elmashad (Environment, Development and Sustainability, 2023)

Experimental and statistical analysis of a solar desalination HDH arrangement with high-speed acceleration centrifugal sprayer - Ammar S. Easa; Reda A. Khalaf-Allah; Salwa M. Mohamed; Mohamed G. Kandel; Waheed S. Barakat; Mohamed I.A. Habba (Desalination, 2023)

Silica Nanoparticle–Induced Reproductive Toxicity in Male Albino Rats via Testicular Apoptosis and Oxidative Stress - Rehab A. Azouz; Reda M. S. Korany; Peter A. Noshy (Biological Trace Element Research, 2023)
Amorphous silica nanoparticles (SiNPs) are being utilized in different fields such as medicine, cosmetics, and foods. However, the causes and mechanisms underlying SiNP testicular damage remain largely unclear. In the present study, we aimed to investigate this issue. Thirty male rats were randomly divided into three groups: control group ( n = 10), 500 ppm SiNP–treated group ( n = 10), and 1000 ppm SiNP–treated group ( n = 10). SiNPs were given orally in drinking water for 30 days. Micronucleus assay was performed on blood RBCs. The concentrations of testicular malondialdehyde (MDA) and glutathione (GSH) and catalase (CAT) activity were measured. Moreover, the histopathological alterations and the expression of apoptotic (caspase-3) and pro-inflammatory and oxidative stress markers (iNOS) in testes and epididymis were analyzed and compared between the three groups. The results showed an increased level of micronucleus frequencies in the 1000 ppm–treated group, as well as increased levels of MDA and decreased activity of CAT and GSH content in testicular tissues in the 1000 ppm–treated group, suggesting DNA damage and oxidative stress mechanisms. Also, there were significant testicular histopathological alterations in this group. Furthermore, 1000-ppm SiNPs could enhance testicular apoptosis, inflammation, and oxidative stress by increasing the expression of apoptotic, pro-inflammatory, and oxidative stress genes including caspase 3 and iNOS in the examined tissue. The lower concentration of SiNPs did not produce any significant biochemical, histopathological, or immunohistochemical alterations whereas 1000-ppm SiNPs resulted in significant testicular changes by exacerbating apoptotic, inflammatory, and oxidative stress–mediated testicular damage.

Efficiency and selectivity of cost-effective Zn-MOF for dye removal, kinetic and thermodynamic approach - Abeer S. Elsherbiny; Ahmed Rady; Reda M. Abdelhameed; Ali H. Gemeay (Environmental Science and Pollution Research, 2023)
Green synthesis of metal–organic frameworks (MOFs) has attracted a lot of attention as a crucial step for practical industrial applications. In this work, green synthesis of zinc(II) metal–organic framework (Zn-MOF) has been carried out at room temperature. The Zn metal (node) was extracted from spent domestic batteries, and the linker was benzene di-carboxylic acid (BDC). The characterization of the as-prepared Zn-MOF was accomplished by PXRD, FT-IR spectroscopy, SEM, TEM, TGA, and nitrogen adsorption at 77 K. All the characterization techniques strongly supported that as-synthesized Zn-MOF using metallic solid waste Zn is similar to that was reported in the literature. The as-prepared Zn-MOF was stable in water for 24 h without any changes in its functional groups and framework. The prepared Zn-MOF was tested for the adsorption of three dyes, two anionic dyes, aniline blue (AB), and orange II (O(II)) as well as methylene blue (MB), an example of cationic dye from aqueous solution. AB has the highest equilibrium adsorbed amount, q e , of value 55.34 mg g −1 at pH = 7 and 25 °C within 40 min. Investigation of the adsorption kinetics indicated that these adsorption processes could be described as a pseudo-second-order kinetic model. Furthermore, the adsorption process of the three dyes was described well by the Freundlich isotherm model. According to the thermodynamic parameters, the adsorption of AB on the prepared Zn-MOF was an endothermic and spontaneous process. In contrast, it was non-spontaneous and exothermic for the uptake of O(II) and MB. This study complements the business case development model of “solid waste to value-added MOFs.”

Prophylactic supplementation of microencapsulated Boswellia serrata and probiotic bacteria in metabolic syndrome rats - Moetazza M. Alshafei; Ahmed M. Mabrouk; Emtenan M. Hanafi; Manal M. Ramadan; Reda M.S. Korany; Seham S. Kassem; Dina Mostafa Mohammed (Food Bioscience, 2023)

Sun CubE OnE: A multi-wavelength synoptic solar micro satellite - L. Giovannelli; F. Berrilli; M. Casolino; F. Curti; D. Del Moro; D. Calchetti; M. Cantoresi; A. D’Ambrosio; G. Francisco; P. Giobbi; L. Marcelli; P. Mazzotta; et al. (Advances in Space Research, 2023)

Oil Spill Identification based on Dual Attention UNet Model Using Synthetic Aperture Radar Images - Amira S. Mahmoud; Sayed A. Mohamed; Reda A. El-Khoriby; Hisham M. AbdelSalam; Ihab A. El-Khodary (Journal of the Indian Society of Remote Sensing, 2023)
Oil spills cause tremendous damage to marine, coastal environments, and ecosystems. Previous deep learning-based studies have addressed the task of detecting oil spills as a semantic segmentation problem. However, further improvement is still required to address the noisy nature of the Synthetic Aperture Radar (SAR) imagery problem, which limits segmentation performance. In this study, a new deep learning model based on the Dual Attention Model (DAM) is developed to automatically detect oil spills in a water body. We enhanced a conventional UNet segmentation network by integrating a dual attention model DAM to selectively highlight the relevant and discriminative global and local characteristics of oil spills in SAR imagery. DAM is composed of a Channel Attention Map and a Position Attention Map which are stacked in the decoder network of UNet. The proposed DAM-UNet is compared with four baselines, namely fully convolutional network, PSPNet, LinkNet, and traditional UNet. The proposed DAM-UNet outperforms the four baselines, as demonstrated empirically. Moreover, the EG-Oil Spill dataset includes a large set of SAR images with 3000 image pairs. The obtained overall accuracy of the proposed method increased by 3.2% and reaches 94.2% compared with that of the traditional UNet. The study opens new development ideas for integrating attention modules into other deep learning tasks, including machine translation, image-based analysis, action recognition, and speech recognition.

Evaluation of antiobesity and hepatorenal protective activities of Salvia officinalis extracts pre-treatment in high-fat diet-induced obese rats - Mohamed S. Othman; Azza M. Khaled; Ghada M. Aleid; Mohamed A. Fareid; Reda A. Hameed; Mohamed S. Abdelfattah; Doaa Ezz Aldin; Ahmed E. Abdel Moneim (Environmental Science and Pollution Research, 2022)

Echinops spinosus effect against diabetes and its hepatorenal complications: total extract and flavonoids fraction - Mohamed S. Othman; Azza M. Khaled; Amal H. Al-Bagawi; Mohamed A. Fareid; Reda A. Hameed; Fatama A. Abu Zahra; Ahmed E. Abdel Moneim (Environmental Science and Pollution Research, 2022)

Impact of some plant powders on Sitophilus granarius (L.) and Rhizopertha dominica (Fab.) for protecting wheat grain - Reda S. Hassan; Thanaa M. Sileem; Amira A. Mikhaiel; Karam Kh.El- Gizawy (International Journal of Tropical Insect Science, 2022)

Impact of plasma irradiation on Tribolium castaneum - Waheed A. A. Sayed; Reda S. Hassan; Thanaa M. Sileem; Birgit A. Rumpold (Journal of Pest Science, 2021)
Radio frequency plasma (RFP) could provide reliable, compact, cost-effective irradiation applications against insect pests of stored food and feed products. Sensitivity of red flour beetle Tribolium castaneum to RFP has been investigated using an irradiation applicator system with the two types of inert gases, argon (Ar) and helium (He), at 100 W for five exposure time levels of 0, 20, 40, 60 and 90 s, respectively. We demonstrated that He RFP was more efficient against T. castaneum than Ar RFP. In addition, a positive correlation was observed between mortality percentages of treated insect stages and exposure times for both He and Ar RFP. The adult stage showed the highest tolerance to RFP irradiation followed by larvae and pupae; however, it was more susceptible than larvae within 24 h after He RFP treatments. The optimum exposure time was 90 s with He RFP, where a full mortality at all tested stages was accomplished, while mortalities of 71.4, 65.3 and 36.7% were recorded for pupae, larvae and adult stage, respectively, after an Ar RFP treatment of 90 s. In case of treated adults, the reproduction rate was higher than treated larvae and pupae. Our findings indicated that He RFP was an effective method for inhibiting T. castaneum development and impacting the insect life cycle and could be considered a promising tool for pest control of stored food.

Toxic Impacts of Amorphous Silica Nanoparticles on Liver and Kidney of Male Adult Rats: an In Vivo Study - Rehab A. Azouz; Reda M. S. Korany (Biological Trace Element Research, 2021)

Replacement of dietary fish oil with plant oils improves the immunological responses and the antioxidant status in Oreochromis niloticus exposed to suboptimal temperature - Rasha M. Reda; Amel El Asely; Ayman S. Salah; Mohamed A. Mahmoud (Fish Physiology and Biochemistry, 2020)

Adulticidal Activity of Atmospheric Plasma Irradiation against the Red Flour Beetle, Tribolium castaneum - Thanaa M. Sileem; Reda S. Hassan; Eman A. Mahmoud (International Journal of Tropical Insect Science, 2020)

Protective potency of Astragalus polysaccharides against tilmicosin- induced cardiac injury via targeting oxidative stress and cell apoptosis-encoding pathways in rat - Ashraf Awad; Samah R. Khalil; Basma M. Hendam; Reda M. Abd El-Aziz; Mohamed M. M. Metwally; Tamer S. Imam (Environmental Science and Pollution Research, 2020)

Effects of Dietary Supplementation of Probiotic Mix and Prebiotic on Growth Performance, Cecal Microbiota Composition, and Protection Against Escherichia coli O78 in Broiler Chickens - Reda Tarabees; Khaled M. Gafar; Mohamed S. EL-Sayed; Awad A. Shehata; Marwa Ahmed (Probiotics and Antimicrobial Proteins, 2019)

Saponin-adjuvanted vaccine protects chickens against velogenic Newcastle disease virus - Wahid H. El-Dabae; Hussein Aly Hussein; Mohammed A. Rohaim; Munir M. El-Safty; Nagwa S. Ata; Ismail M. Reda (Archives of Virology, 2018)

Adsorption studies on the removal of COD and BOD from treated sewage using activated carbon prepared from date palm waste - Abd ElAziz A. Nayl; Reda A. Elkhashab; Tamer El Malah; Sobhy M. Yakout; Mohamed A. El-Khateeb; Mahmoud M. S. Ali; Hazim M. Ali (Environmental Science and Pollution Research, 2017)

Chemosystematic significance of flavonoids isolated from Diplotaxis acris (Brassicaceae) and related taxa - Sameh R. Hussein; Mona M. Marzouk; Mona E.S. Kassem; Rasha R. Abdel Latif; Reda S. Mohammed (Natural Product Research, 2017)

Enhance Efficiency of Solar Cell Using Luminescence PbS Quantum Dots Concentrators - S. M. Reda (Journal of Fluorescence, 2015)

Trematodes from Red Sea Fishes: Neohypocreadium aegyptense n. sp. (Lepocreadiidae), Fairfaxia cribbi n. sp. and Macvicaria chrysophrys (Nagaty & Abdel-Aal, 1969) (Opecoelidae) - Reda M. El-S. Hassanine; David I. Gibson (Systematic Parasitology, 2005)

Trematodes of Red Sea fishes: Hexangium brayi n. sp. (Angiodictyidae Looss, 1902) and Siphodera aegyptensis n. sp. (Cryptogonimidae Ward, 1917), with a review of their genera - Reda M. El-S. Hassanine; David I. Gibson (Systematic Parasitology, 2005)

Prediction of a mesoscale convective system over catalonia (Northeastern Spain) with a nested numerical model - B. Codina; M. Aran; S. Young; A. Redao (Meteorology and Atmospheric Physics, 1997)

Effect of avermectin and dicofol on the immatures of the predacious miteAmblyseius gossipi with a special reference to the secondary poisoning effect on the adult female [Acari: Phytoseiidae] - A. S. Reda; E. M. El-Banhawy (BioControl, 1988)

A new diet for reproduction of two predaceous mitesAmblyseius gossipi andAgistemus exsertus [Acari: Phytoseiidae, stigmaeidae] - A. H. Rasmy; M. E. Elbagoury; A. S. Reda (BioControl, 1987)